(untitled) (Dhaka University Journal of Business Studies, 2026)
This study examines the green initiatives within Leadership in Energy and Environmental Design (LEED) certified Readymade Garment (RMG) factories in Bangladesh, exploring the connection between these initiatives and sustainable development. Despite the critical role of the RMG sector in the economy of Bangladesh, there is a paucity of research on green practices. Thus, the objectives of this study were to catalog the green initiatives undertaken by these factories, identify the key drivers of such initiatives, and assess their contribution to sustainable development. This study applied case study methods, taking 10 LEED-certified RMG factories with triangulation by a focused group discussion and key informant interviews. Findings reveal that LEED-certified factories have invested in eco-friendly construction, energy conservation through solar power and natural lighting, advanced effluent treatment, sustainable transportation, innovative waste-to-energy solutions, plastic recovery, and afforestation initiatives. These strategies exemplify a strong commitment to environmental protection while delivering notable socio-economic advantages, thus fostering comprehensive sustainable development within the industry. The study highlights the critical role of green initiatives, offers actionable insights, and provides a basis for future studies for RMG and other sectors in Bangladesh. Journal of Business Studies, Vol. XLIV, No. 1, 2025 Page 31-52